"When a Patient Is Unable to Work in the Transference": Dr. Lament's Response. Issue 1 (1st January 2020) - Lament, Claudia
ABSTRACT: This piece addresses a prominent question that arose from the author's presentation of her paper, "Turning Points in Adolescent Analysis". Specifically, the adolescent patient who was the subject of the paper was unable to work within the transference relationship, despite the author/analyst's pursuit of this feature of their exchange. Reasons for the patient's inability to do this are discussed, including the patient's neuropsychological challenges and ADHD and their impact on psychic structure formation and her concrete-ism. More useful to the patient were mirroring transference interventions as well as those which capitalized on assisting the development of inchoate ego structures and functions; and aiding the transformational pull forward into young adulthood. A child and adolescent analyst (as well as an analyst of adult patients) must choose arrows from her quiver of therapeutic action based upon which ones the patient is capable of using, and which ones target the nature and symptoms of the patient's disturbance which prevent her from using the transference relationship . The author draws from Anna Freud as well as contemporary thinkers on this topic.